Pengembangan Sistem Reservasi Penginapan untuk Youth Hostel Griya Brawijaya - Osa Prisdyana; Ismiarta Aknuranda; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Youth Hostel Griya Brawijaya is a lodging facility managed by a students' cooperative of Brawijaya University. Based on the results of interviews with the manager of Youth Hostel Griya Brawijaya, can be concluded that all transactions to reserve the rooms remains to be received manually till now, including process of management of reservation data, types of room data, rooms data, forfeits data, payment data, and report of reservation recapitulation. It frequently cause some problems such as amount of time is needed to process the reservations, seek, make the notes, and recap the data which cause the process of reservation in Youth Hostel Griya Brawijaya did not run in optimal. The solutions to deal with this problems are by improving a web-based lodging reservation system refer to the necessary by doing some modification to the business process flow. This study begins by analyzing current business processes to find the requirements as needed, then proceed with design and implementation phase. The next phase is do a test for system using validation testing and compatibility testing. The results of validation testing showed that the system could run well in accordance with the functionality. And the result of compatibility testing is a system could run well on some versions of different browsers.